Investigating dynamical deformations of tumor cells in circulation: predictions from a theoretical model - Rejniak, Katarzyna A. (Frontiers in Oncology, 2012)
It is inevitable for the tumor cells to deal with various mechanical forces in order to move from the primary to metastatic site. In particular, the circulating tumor cells (CTCs) that have detached from the primary tumor and entered into the bloodstream need to survive in a completely new microenvironment. They must withstand the haemodynamic forces and overcome the effects of fluid shear before they can leave the vascular system (extravasate) to establish the new metastatic foci. One of the hypotheses of tumor cell extravasation process is via the, so called, “adhesion cascade” that was formulated and observed in the context of leukocytes circulating in the vascular system. During this process, the cell needs to switch between various locomotion strategies, from floating with the blood stream, to rolling on the endothelial wall, to tumor cell arrest and crawling, and finally tumor cell transmigration through the endothelial layer. The goal of this project is to use computational mechanical modeling to investigate fundamental biophysical parameters of tumor cells in circulation. As a first step to build a robust in silico model we consider a single cell exposed to the blood flow. We examine parameters related to structure of the actin network, cell nucleus and adhesion links between the tumor and endothelial cells that allow for successful transition between different transport modes of the adhesion cascade.